Ein neuer Adoretus aus Afghanistan (Coleoptera: Scarabaeidae, Adoretinae). - Machatschke, Johann W. (Contributions to Entomology = Beiträge zur Entomologie, 1958)
A new Adoretus from Afghanistan (Adoretus afghanus) is described and compared with the related species Adoretus incurvatus Ohs., progrediens Ohs., simplex Arrow, which form a natural group (Adoretus-simplex-group). Nomenclatural Acts afghanus Machatschke, 1958 (Adoretus), spec. n.